The Role of Fiqh in Anti-Corruption Education as an Effort to Realize Good Governance in the Context of Halal City Concept - Khalid Rahman; Albar Adetary Hasibuan; Abdul Madjid; Lutfi Asnan Qodri; Sahril Kamal (AIBPM Publisher, 2024)
This study explores the potential of fiqh (Islamic jurisprudence) in anti-corruption education as a tool to promote good governance within the context of a Halal City initiative. The research is motivated by the prevalence of corruption in Indonesia, exemplified by the high number of corruption cases in Malang City (41 out of 45 people accused in 2018). The study adopts a mixed-methods approach, employing library research, interviews, and surveys to analyze public understanding of fiqh and the Halal City concept in Malang. Quantitative data is analyzed using Structural Equation Modeling (SEM). The findings reveal a mixed public response to incorporating fiqh formulations directly into regulations (coefficient: 0.16). However, the study highlights a promising alternative: implementing fiqh principles within anti-corruption education programs shows a significant positive effect on public awareness (coefficient: 0.93). A key challenge identified is the negative evaluation of good governance within the current Halal City concept (coefficient: -0.64), despite public optimism regarding the initiative's overall goals (coefficient: 0.62). It is suggested to study these factors which can inform policymakers and bridge the gap between program execution and public expectations. Ultimately, this can lead to a more successful and well-received Halal City initiative that contributes to broader anti-corruption efforts.